Does creative thinking contribute to the academic integrity of education students? - Eshet, Yovav; Margaliot, Adva (Frontiers in Psychology, 2022)
The current research focuses on the nature of the relationship comprising personality traits, creative thinking, and academic integrity. Scholars have confirmed that personality traits and creative thinking correlate positively with academic integrity. However, a discussion of academic integrity, personality traits and creative thinking are missing in the scholarly literature. This study used a questionnaire survey based on the Big Five Factor to identify personality characteristics, the Academic Integrity Inventory, and the Torrance Tests of Creative Thinking. The sample included 976 students studying in four academic colleges in Israel, of which two are teacher training colleges and two colleges awarding a degree in education. The findings show that most of the students (71%) reported they had cheated at some point during their academic studies, and only one-fifth (21%) thought that they would condemn their peers’ lack of integrity. Creative thinking students and emotionally stable persons tend to be more ethical. Hence, we conclude that it is recommended to deliver creative thinking courses in the teacher’s educational training programs to improve creative thinking levels, reduce academic dishonesty, and create more effective curricula.